PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SIKAP DISIPLIN SISWA KELAS VII SMP AL-FURQON MADRASATUL QUR’AN TEBUIRENG JOMBANG - Muhammad 'Alamulhuda; Burhanuddin Ridlwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) teachers bear responsibilities that exceed those of conventional instructors, particulary in pesantren-based school settings where religious values are not merely taught in classroom but lived throughout the day. This study aims to critically analyze the role of PAI teachers in improving the disciplinary attitudes of seventh-grade students at SMP Al-Furqon Madrasatul Qur’an Tebuireng Jombang through three core questions: (1) how PAI teachers instill discipline-related values in students; (2) how students’ disciplinary attitudes have improved; and (3) what factors support or hinder this role. A qualitative case study design was employed. Data were gathered through participatory observation, in-depth interviews, and documentation involving the school principal, the PAI teacher, and seventh-grade students. Analysis followed the Miles and Huberman interactive model, validated through source, technique, and time triangulation. Findings reveal that the PAI teacher’s role in shaping student discipline operates through five mutually reinforcing pathways: exemplary conduct (uswah hasanah), integration of Islamic values into all learning content, habituation strategies combined with reflective discussion, personal guidance that is educational and persuasive in nature, and the integration of worship with academic responsibility. The impact is visible in students’ gradual progression from extrinsic discipline, rooted in fear of sanctions, toward intrinsic discipline grounded in spiritual awareness and moral responsibility before Allah SWT. Supporting factors include the pesantren’s religious ecosystem, integrative institutional policies, and teacher-parent collaboration; primary obstacles include heterogeneous student character backgrounds, adaptation pressures as new santri, and peer influence.